TEMBUNG LAN GAMBARE KAMUS VISUAL RAGAM DIKSI BAHASA JAWA TINGKAT NGOKO - Jatmiko, Edi (DeKaVe, 2017)
Java language as a motherÂ language, has a complicated character, and terraced difficult even for Javanese society itself. The level of complexity in the Java language system is one of the factors that led to the Java language is considered less desirable and not match the needs of the times by the Java community itself. This difficulty is caused by one of the Java language has a complete vocabulary, diction diverse, in one term in Indonesian, can be assorted due to the mention of the Java language that caused chronology. Javanese society has the ability to mark the various forms of work in different terms though just because of small differences. Diction of the diversity of conditions in the Java language ngoko level, ie the level of the language most widely used Java community need for adequate instructional media. One of the gaps that can be addressed in greater depth is how to bring learning the Java language into a form that is easily understood visual communication method is to create a visual dictionary of the Java language.